Antibacterial polyester wadding and manufacturing process thereof
By using a combination of nanosilver and specific adhesives in the sprayed cotton, the problem of bacteria breeding of sprayed cotton is solved, and effective inhibition of Staphylococcus epidermis and E. coli is achieved, ensuring the safety of the product and production process. Adaptability, while improving the performance of glue-sprayed cotton, such as finish and dry and wet strength.
Patent Information
- Application Number
- CN202411402416.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
AI Technical Summary
After use, sprayed glue cotton is prone to breed bacteria, affecting the user experience and causing harm to the environment and the human body.
Using a combination of nanosilver and specific adhesives, the adhesive is sprayed by spraying machines and dried on the fiber layer, followed by drying in the nanosilver solution to prepare antibacterial sprayed cotton, nanosilver including silver nitrate, citric acid, Polyvinylpyrrolidone, urea, sodium metaphosphate and sodium hypophosphite, and binders include methyl methacrylate, butyl acrylate, sodium dodecyl sulfate, N-carboxymethacrylamide, potassium persulfate and ammonia water.
Effectively inhibit the growth of Staphylococcus epidermis and E. coli, safe and non-toxic, the adhesive is non-toxic, odorless, and has excellent mechanical stability. It is suitable for production process requirements. The made glue-sprayed cotton is smooth, has high dry and wet strength and good elasticity. And it does not shrink.
Abstract
Description
Technical Field
[0001] The invention relates to the manufacturing field of spray-bonded cotton, and in particular to an antibacterial spray-bonded cotton and a manufacturing process thereof. Background Art
[0002] Spray-bonded cotton, also known as spray-bonded cotton, is a type of non-woven fabric. The principle of the structure of spray-bonded cotton is to spray the adhesive on both sides of the fluffy fiber layer. Due to the certain pressure during spraying and the suction force during the vacuum absorption of liquid at the bottom, the adhesive can also penetrate into the inside of the fiber layer.
[0003] After long-term use, spray-bonded cotton will breed bacteria due to moisture, which will affect the user experience and cause harm to the environment and human body. Summary of the invention
[0004] The main purpose of the present invention is to provide an antibacterial spray-bonded cotton and a manufacturing process thereof, which can effectively solve the problems in the background technology.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] An antibacterial spray-bonded cotton comprises a fiber layer, nano silver and an adhesive, wherein the nano silver comprises 20-40 parts of silver nitrate, 30-50 parts of citric acid, 5-10 parts of polyvinyl pyrrolidone, 2-10 parts of urea, 5-15 parts of sodium metaphosphate and 5-15 parts of sodium hypophosphite, and the adhesive comprises 10-30 parts of methyl methacrylate, 30-50 parts of butyl acrylate, 10-20 parts of sodium dodecyl sulfate, 2-10 parts of N-carboxymethyl acrylamide, 2-10 parts of potassium persulfate, 2-10 parts of ammonia water and 10-30 parts of deionized water.
[0007] Preferably, the ratio of nanosilver to adhesive is 1:1.
[0008] Preferably, the nanosilver comprises 30 parts of silver nitrate, 40 parts of citric acid, 5 parts of polyvinyl pyrrolidone, 5 parts of urea, 10 parts of sodium metaphosphate, and 10 parts of sodium hypophosphite, and the adhesive comprises 20 parts of methyl methacrylate, 40 parts of butyl acrylate, 15 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 5 parts of potassium persulfate, 5 parts of ammonia water, and 10 parts of deionized water.
[0009] Preferably, the nanosilver comprises 25 parts of silver nitrate, 30 parts of citric acid, 10 parts of polyvinyl pyrrolidone, 5 parts of urea, 15 parts of sodium metaphosphate, and 15 parts of sodium hypophosphite; the adhesive comprises 15 parts of methyl methacrylate, 30 parts of butyl acrylate, 10 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 5 parts of potassium persulfate, 5 parts of ammonia water, and 30 parts of deionized water.
[0010] Preferably, the nanosilver comprises 20 parts of silver nitrate, 50 parts of citric acid, 5 parts of polyvinyl pyrrolidone, 2 parts of urea, 13 parts of sodium metaphosphate, and 10 parts of sodium hypophosphite; the adhesive comprises 10 parts of methyl methacrylate, 50 parts of butyl acrylate, 10 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 10 parts of potassium persulfate, 5 parts of aqueous ammonia, and 10 parts of deionized water.
[0011] A manufacturing process of antibacterial spray-bonded cotton, comprising the following steps:
[0012] S1: Prepare the equipment for preparation: electric stirrer, thermometer, reflux condenser, nitrogen tube, dropping funnel, 250ml four-necked flask, dryer, spray machine;
[0013] S2: Preparation of adhesive: an electric stirrer, a thermometer, a reflux condenser, a nitrogen tube, and a dropping funnel are placed in a 250 ml four-necked flask, methyl methacrylate, butyl acrylate, sodium dodecyl sulfate, N-carboxymethyl acrylamide, and aqueous ammonia are added to the 250 ml four-necked flask according to their weight fractions, nitrogen is passed through the flask, the mixture is stirred, and heated to 82-87° C., potassium persulfate dissolved in deionized water is added dropwise within 10 min, the mixture is polymerized, and the mixture is cooled to 25° C. and filtered to obtain an adhesive;
[0014] S3: Preparation of nanosilver: Dissolve silver nitrate, citric acid, polyvinyl pyrrolidone, urea and sodium metaphosphate in deionized water according to their mass fractions, add them into a 250ml four-necked flask, heat to 70°C and stir for 5min, then dissolve sodium hypophosphite in deionized water, slowly add it into the 250ml four-necked flask, heat to 80°C and keep for 1h, thereby completing the preparation of nanosilver;
[0015] S4: Preparation of antibacterial spray-bonded cotton: Spray the adhesive on both sides of the fiber layer by a spraying machine. After spraying, quickly dry the moisture in a dryer at a temperature of 120°C. After drying, place the fiber layer in a nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. Then dilute the nanosilver solution with water to 0.1%, then place the fiber layer in the nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. After drying, take it out to complete the preparation.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] In the present invention, the prepared nano silver has an excellent ability to inhibit the growth of Staphylococcus epidermidis and Escherichia coli, and is safe and non-toxic. The nano silver can penetrate the cell wall and combine with the basic enzymes used for their breathing to suffocate the bacteria and viruses to death. The prepared adhesive has the characteristics of being non-toxic, tasteless, excellent in mechanical stability, good in storage stability, etc., and is suitable for the production process requirements of various spray-bonded cotton. In addition, the prepared spray-bonded cotton is smooth and beautiful, has high dry and wet strength, good elasticity, does not shrink, and has a good film-forming feel. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The invention relates to an antibacterial spray-bonded cotton, comprising a fiber layer, nano silver and an adhesive, wherein the nano silver comprises 20-40 parts of silver nitrate, 30-50 parts of citric acid, 5-10 parts of polyvinyl pyrrolidone, 2-10 parts of urea, 5-15 parts of sodium metaphosphate and 5-15 parts of sodium hypophosphite, and the adhesive comprises 10-30 parts of methyl methacrylate, 30-50 parts of butyl acrylate, 10-20 parts of sodium dodecyl sulfate, 2-10 parts of N-carboxymethyl acrylamide, 2-10 parts of potassium persulfate, 2-10 parts of ammonia water and 10-30 parts of deionized water, and the ratio of the nano silver to the adhesive is 1:1.
[0020] The nanosilver includes 30 parts of silver nitrate, 40 parts of citric acid, 5 parts of polyvinyl pyrrolidone, 5 parts of urea, 10 parts of sodium metaphosphate, and 10 parts of sodium hypophosphite. The adhesive includes 20 parts of methyl methacrylate, 40 parts of butyl acrylate, 15 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 5 parts of potassium persulfate, 5 parts of ammonia water, and 10 parts of deionized water.
[0021] The nanosilver includes 25 parts of silver nitrate, 30 parts of citric acid, 10 parts of polyvinyl pyrrolidone, 5 parts of urea, 15 parts of sodium metaphosphate, and 15 parts of sodium hypophosphite. The adhesive includes 15 parts of methyl methacrylate, 30 parts of butyl acrylate, 10 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 5 parts of potassium persulfate, 5 parts of ammonia water, and 30 parts of deionized water.
[0022] The nanosilver includes 20 parts of silver nitrate, 50 parts of citric acid, 5 parts of polyvinyl pyrrolidone, 2 parts of urea, 13 parts of sodium metaphosphate, and 10 parts of sodium hypophosphite. The adhesive includes 10 parts of methyl methacrylate, 50 parts of butyl acrylate, 10 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 10 parts of potassium persulfate, 5 parts of ammonia water, and 10 parts of deionized water.
[0023] A manufacturing process of antibacterial spray-bonded cotton comprises the following steps:
[0024] S1: Prepare the equipment for preparation: electric stirrer, thermometer, reflux condenser, nitrogen tube, dropping funnel, 250ml four-necked flask, dryer, spray machine;
[0025] S2: Preparation of adhesive: an electric stirrer, a thermometer, a reflux condenser, a nitrogen tube, and a dropping funnel are placed in a 250 ml four-necked flask, methyl methacrylate, butyl acrylate, sodium dodecyl sulfate, N-carboxymethyl acrylamide, and aqueous ammonia are added to the 250 ml four-necked flask according to their weight fractions, nitrogen is passed through the flask, the mixture is stirred, and heated to 82-87° C., potassium persulfate dissolved in deionized water is added dropwise within 10 min, the mixture is polymerized, and the mixture is cooled to 25° C. and filtered to obtain an adhesive;
[0026] S3: Preparation of nanosilver: Dissolve silver nitrate, citric acid, polyvinyl pyrrolidone, urea and sodium metaphosphate in deionized water according to their mass fractions, add them into a 250ml four-necked flask, heat to 70°C and stir for 5min, then dissolve sodium hypophosphite in deionized water, slowly add it into the 250ml four-necked flask, heat to 80°C and keep for 1h, thereby completing the preparation of nanosilver;
[0027] S4: Preparation of antibacterial spray-bonded cotton: Spray the adhesive on both sides of the fiber layer by a spraying machine. After spraying, quickly dry the moisture in a dryer at a temperature of 120°C. After drying, place the fiber layer in a nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. Then dilute the nanosilver solution with water to 0.1%, then place the fiber layer in the nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. After drying, take it out to complete the preparation. Specific embodiment one:
[0029] An antibacterial spray-bonded cotton comprises a fiber layer, nano-silver and an adhesive, wherein the nano-silver comprises 20 parts of silver nitrate, 50 parts of citric acid, 5 parts of polyvinyl pyrrolidone, 2 parts of urea, 13 parts of sodium metaphosphate and 10 parts of sodium hypophosphite, and the adhesive comprises 10 parts of methyl methacrylate, 50 parts of butyl acrylate, 10 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 10 parts of potassium persulfate, 5 parts of ammonia water and 10 parts of deionized water, and the ratio of nano-silver to adhesive is 1:1.
[0030] A manufacturing process of antibacterial spray-bonded cotton comprises the following steps:
[0031] S1: Prepare the equipment for preparation: electric stirrer, thermometer, reflux condenser, nitrogen tube, dropping funnel, 250ml four-necked flask, dryer, spray machine;
[0032] S2: Preparation of adhesive: an electric stirrer, a thermometer, a reflux condenser, a nitrogen tube, and a dropping funnel are placed in a 250 ml four-necked flask, methyl methacrylate, butyl acrylate, sodium dodecyl sulfate, N-carboxymethyl acrylamide, and aqueous ammonia are added to the 250 ml four-necked flask according to their weight fractions, nitrogen is passed through the flask, the mixture is stirred, and heated to 82-87° C., potassium persulfate dissolved in deionized water is added dropwise within 10 min, the mixture is polymerized, and the mixture is cooled to 25° C. and filtered to obtain an adhesive;
[0033] S3: Preparation of nanosilver: Dissolve silver nitrate, citric acid, polyvinyl pyrrolidone, urea and sodium metaphosphate in deionized water according to their mass fractions, add them into a 250ml four-necked flask, heat to 70°C and stir for 5min, then dissolve sodium hypophosphite in deionized water, slowly add it into the 250ml four-necked flask, heat to 80°C and keep for 1h, thereby completing the preparation of nanosilver;
[0034] S4: Preparation of antibacterial spray-bonded cotton: Spray the adhesive on both sides of the fiber layer by a spraying machine. After spraying, quickly dry the moisture in a dryer at a temperature of 120°C. After drying, place the fiber layer in a nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. Then dilute the nanosilver solution with water to 0.1%, then place the fiber layer in the nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. After drying, take it out to complete the preparation. Specific embodiment 2:
[0036] An antibacterial spray-bonded cotton comprises a fiber layer, nano-silver and an adhesive, wherein the nano-silver comprises 25 parts of silver nitrate, 30 parts of citric acid, 10 parts of polyvinyl pyrrolidone, 5 parts of urea, 15 parts of sodium metaphosphate and 15 parts of sodium hypophosphite, and the adhesive comprises 15 parts of methyl methacrylate, 30 parts of butyl acrylate, 10 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 5 parts of potassium persulfate, 5 parts of ammonia water and 30 parts of deionized water, and the ratio of nano-silver to adhesive is 1:1.
[0037] A manufacturing process of antibacterial spray-bonded cotton comprises the following steps:
[0038] S1: Prepare the equipment for preparation: electric stirrer, thermometer, reflux condenser, nitrogen tube, dropping funnel, 250ml four-necked flask, dryer, spray machine;
[0039] S2: Preparation of adhesive: an electric stirrer, a thermometer, a reflux condenser, a nitrogen tube, and a dropping funnel are placed in a 250 ml four-necked flask, methyl methacrylate, butyl acrylate, sodium dodecyl sulfate, N-carboxymethyl acrylamide, and aqueous ammonia are added to the 250 ml four-necked flask according to their weight fractions, nitrogen is passed through the flask, the mixture is stirred, and heated to 82-87° C., potassium persulfate dissolved in deionized water is added dropwise within 10 min, the mixture is polymerized, and the mixture is cooled to 25° C. and filtered to obtain an adhesive;
[0040] S3: Preparation of nanosilver: Dissolve silver nitrate, citric acid, polyvinyl pyrrolidone, urea and sodium metaphosphate in deionized water according to their mass fractions, add them into a 250ml four-necked flask, heat to 70°C and stir for 5min, then dissolve sodium hypophosphite in deionized water, slowly add it into the 250ml four-necked flask, heat to 80°C and keep for 1h, thereby completing the preparation of nanosilver;
[0041] S4: Preparation of antibacterial spray-bonded cotton: Spray the adhesive on both sides of the fiber layer by a spraying machine. After spraying, quickly dry the moisture in a dryer at a temperature of 120°C. After drying, place the fiber layer in a nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. Then dilute the nanosilver solution with water to 0.1%, then place the fiber layer in the nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. After drying, take it out to complete the preparation. Specific embodiment three:
[0043] An antibacterial spray-bonded cotton comprises a fiber layer, nano-silver and an adhesive, wherein the nano-silver comprises 30 parts of silver nitrate, 40 parts of citric acid, 5 parts of polyvinyl pyrrolidone, 5 parts of urea, 10 parts of sodium metaphosphate and 10 parts of sodium hypophosphite, and the adhesive comprises 20 parts of methyl methacrylate, 40 parts of butyl acrylate, 15 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 5 parts of potassium persulfate, 5 parts of ammonia water and 10 parts of deionized water, and the ratio of nano-silver to adhesive is 1:1.
[0044] A manufacturing process of antibacterial spray-bonded cotton comprises the following steps:
[0045] S1: Prepare the equipment for preparation: electric stirrer, thermometer, reflux condenser, nitrogen tube, dropping funnel, 250ml four-necked flask, dryer, spray machine;
[0046] S2: Preparation of adhesive: an electric stirrer, a thermometer, a reflux condenser, a nitrogen tube, and a dropping funnel are placed in a 250 ml four-necked flask, methyl methacrylate, butyl acrylate, sodium dodecyl sulfate, N-carboxymethyl acrylamide, and aqueous ammonia are added to the 250 ml four-necked flask according to their weight fractions, nitrogen is passed through the flask, the mixture is stirred, and heated to 82-87° C., potassium persulfate dissolved in deionized water is added dropwise within 10 min, the mixture is polymerized, and the mixture is cooled to 25° C. and filtered to obtain an adhesive;
[0047] S3: Preparation of nanosilver: Dissolve silver nitrate, citric acid, polyvinyl pyrrolidone, urea and sodium metaphosphate in deionized water according to their mass fractions, add them into a 250ml four-necked flask, heat to 70°C and stir for 5min, then dissolve sodium hypophosphite in deionized water, slowly add it into the 250ml four-necked flask, heat to 80°C and keep for 1h, thereby completing the preparation of nanosilver;
[0048] S4: Preparation of antibacterial spray-bonded cotton: Spray the adhesive on both sides of the fiber layer by a spraying machine. After spraying, quickly dry the moisture in a dryer at a temperature of 120°C. After drying, place the fiber layer in a nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. Then dilute the nanosilver solution with water to 0.1%, then place the fiber layer in the nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. After drying, take it out to complete the preparation.
[0049] The performance of the spray-bonded cotton prepared by the present invention is compared with the spray-bonded cotton on the market, wherein the specific embodiments 1 to 3 of the present invention are recorded as embodiments 1-3, and the spray-bonded cotton on the market is recorded as comparative example 1. The following is a comparison table:
[0050] Escherichia coli inhibition rate (%) Staphylococcus aureus inhibition rate (%) Mildew resistance Example 1 99.54 98.76 No mildew Example 2 98.87 99.61 No mildew Example 3 98.42 99.66 No mildew Comparative Example 1 84.33 84.67 Slight mildew
[0051] It can be seen that the antibacterial performance of the spray-bonded cotton prepared by the present invention is relatively excellent.
[0052] The nano silver prepared by the present invention has an excellent ability to inhibit the growth of Staphylococcus epidermidis and Escherichia coli, and is safe and non-toxic. The nano silver can penetrate the cell wall and combine with the basic enzymes used for their breathing to suffocate the bacteria and viruses to death. The prepared adhesive has the characteristics of being non-toxic, tasteless, excellent in mechanical stability, good in storage stability, etc., and is suitable for the production process requirements of various spray-bonded cotton. The prepared spray-bonded cotton is smooth and beautiful, has high dry and wet strength, good elasticity, does not shrink, and has a good film-forming feel.
[0053] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An antibacterial spray-bonded cotton, characterized in that: The invention comprises a fiber layer, nano silver and an adhesive, wherein the nano silver comprises 20-40 parts of silver nitrate, 30-50 parts of citric acid, 5-10 parts of polyvinyl pyrrolidone, 2-10 parts of urea, 5-15 parts of sodium metaphosphate and 5-15 parts of sodium hypophosphite, and the adhesive comprises 10-30 parts of methyl methacrylate, 30-50 parts of butyl acrylate, 10-20 parts of sodium dodecyl sulfate, 2-10 parts of N-carboxymethyl acrylamide, 2-10 parts of potassium persulfate, 2-10 parts of ammonia water and 10-30 parts of deionized water.
2. The antibacterial spray-bonded cotton according to claim 1, characterized in that: The ratio of nano silver to adhesive is 1:
1.
3. The antibacterial spray-bonded cotton according to claim 1, characterized in that: The nanosilver comprises 30 parts of silver nitrate, 40 parts of citric acid, 5 parts of polyvinyl pyrrolidone, 5 parts of urea, 10 parts of sodium metaphosphate, and 10 parts of sodium hypophosphite; the adhesive comprises 20 parts of methyl methacrylate, 40 parts of butyl acrylate, 15 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 5 parts of potassium persulfate, 5 parts of ammonia water, and 10 parts of deionized water.
4. The antibacterial spray-bonded cotton according to claim 1, characterized in that: The nanosilver comprises 25 parts of silver nitrate, 30 parts of citric acid, 10 parts of polyvinyl pyrrolidone, 5 parts of urea, 15 parts of sodium metaphosphate, and 15 parts of sodium hypophosphite; the adhesive comprises 15 parts of methyl methacrylate, 30 parts of butyl acrylate, 10 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 5 parts of potassium persulfate, 5 parts of ammonia water, and 30 parts of deionized water.
5. The antibacterial spray-bonded cotton according to claim 1, characterized in that: The nano silver comprises 20 parts of silver nitrate, 50 parts of citric acid, 5 parts of polyvinyl pyrrolidone, 2 parts of urea, 13 parts of sodium metaphosphate, and 10 parts of sodium hypophosphite; the adhesive comprises 10 parts of methyl methacrylate, 50 parts of butyl acrylate, 10 parts of sodium dodecyl sulfate, 5 parts of N-carboxymethyl acrylamide, 10 parts of potassium persulfate, 5 parts of ammonia water, and 10 parts of deionized water.
6. A process for manufacturing antibacterial spray-bonded cotton according to any one of claims 1 to 5, characterized in that: The steps include: S1: Prepare the equipment for preparation: electric stirrer, thermometer, reflux condenser, nitrogen tube, dropping funnel, 250ml four-necked flask, dryer, spray machine; S2: Preparation of adhesive: an electric stirrer, a thermometer, a reflux condenser, a nitrogen tube, and a dropping funnel are placed in a 250 ml four-necked flask, methyl methacrylate, butyl acrylate, sodium dodecyl sulfate, N-carboxymethyl acrylamide, and aqueous ammonia are added to the 250 ml four-necked flask according to their weight fractions, nitrogen is passed through the flask, the mixture is stirred, and heated to 82-87° C., potassium persulfate dissolved in deionized water is added dropwise within 10 min, the mixture is polymerized, and the mixture is cooled to 25° C. and filtered to obtain an adhesive; S3: Preparation of nanosilver: Dissolve silver nitrate, citric acid, polyvinyl pyrrolidone, urea and sodium metaphosphate in deionized water according to their mass fractions, add them into a 250ml four-necked flask, heat to 70°C and stir for 5min, then dissolve sodium hypophosphite in deionized water, slowly add it into the 250ml four-necked flask, heat to 80°C and keep for 1h, thereby completing the preparation of nanosilver; S4: Preparation of antibacterial spray-bonded cotton: Spray the adhesive on both sides of the fiber layer by a spraying machine. After spraying, quickly dry the moisture in a dryer at a temperature of 120°C. After drying, place the fiber layer in a nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. Then dilute the nanosilver solution with water to 0.1%, then place the fiber layer in the nanosilver solution, take it out after 30 seconds, and quickly dry the moisture at a temperature of 120°C. After drying, take it out to complete the preparation.